Cross contamination of cytological smears, with automated staining machines and bulk manual staining procedures. With a specific study of the problems of the Cytotek and the Shandon Elliott staining machines. - Husain, O A (1978)
Further development of an individual staining machine is to be strongly encouraged but meanwhile, using bulk stainers, frequent changing of wash fluids and staining solutions, particularly leading up to and following the haematoxylin pot, is essential to reduce the risk of cross contamination. Certain smears, such as from semen or from serous fluids where malignancy is suspected or known, must be stained on separate racks. In some laboratories it is the rule not to stain semen or serous fluids in bulk staining machines at all and this may have to become the rule everywhere until we are provided with safe individual slide stainers.